FUNGSI TINDAK TUTUR DIREKTIF PERAWAT TERHADAP PASIEN DI RUANG FISIOTERAPI RSU HAJI MEDAN–SUMATRA UTARA - Arni Chairul (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2018)
In communicating activities certainly can not be separated from the theory of speech acts. Speech acts as a form of communication event is not an event that happens by itself, but has a function, contains a specific purpose can cause influence or effect on the said partner. The speech acts is a theory that tries to study the meaning of language based on the relationship of speech with the actions performed by the speaker.Language is used by speakers to convey specific intentions to speech partners such as ordering, begging, asking, and etc.Such speech acts as speech acts are grouped into speech acts directive. Speech from a (speaker) is of course not merely the origin of speech, but it contains certain intentions.The classification of speech acting speech function are : competitive,convivial, collaborative, conflictive.The purpose of this study was to identify the function of speech acts of the nurse directive to the patient in the physiotherapy room at RSU. Haji Medan - North Sumatera.This research is a qualitative research using descriptive and comparative method. From the data analysis found the function of speech act directive, competitive 'compete' with its subfunctions to govern and ask; and collaborative functions 'in collaboration' with its subfunctions stating, teaching, reporting and announcing. From the discussion it is suggested that nurses use speech act directive that has indicators of politeness in Indonesian language so that the function of acting speech directive can be achieved in conveying the intent and purpose to the patient.